2001
DOI: 10.1212/wnl.56.12.1690
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Alzheimer’s disease in very elderly people

Abstract: The prevalence of neuropathologically defined AD is higher than that reported in most previous studies based on clinical diagnosis. The discrepancy between the neuropathologic and clinical diagnoses of AD in very elderly subjects may affect the results of population-based studies. The APOE genotype has a strong effect on the prevalence of neuropathologically defined AD, even after 90 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(110 citation statements)
references
References 39 publications
3
105
1
1
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13][14][15] Preliminary studies that compared the strength of association between dementia diagnosis or cognitive performance and AD neuropathology (neuritic plaques and neurofibrillary tangles) between the young old and the oldest old suggest that the association is weaker among the oldest old 6,13 ; however, these studies were limited by small to moderate size and considered…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15] Preliminary studies that compared the strength of association between dementia diagnosis or cognitive performance and AD neuropathology (neuritic plaques and neurofibrillary tangles) between the young old and the oldest old suggest that the association is weaker among the oldest old 6,13 ; however, these studies were limited by small to moderate size and considered…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have noted that close to half of demented individuals in the tenth decade are likely to have no obvious pathology to explain their cognitive and functional loss [30,31]. Conversely, approximately one of every three non-demented individuals at age 85 have been reported to have senile plaques and neurofibrillary tangles at autopsy, suggesting a pathological diagnosis of AD despite the lack of clear clinical dementia syndrome [31][32][33]. Initial results in a small group of centenarians also showed that about one third of non-demented participants meet pathological criteria for AD [34].…”
Section: Clinical-pathological Correleations In the Oldest-oldmentioning
confidence: 99%
“…In the Oregon Brain Aging Study [35], participants are aged 85 and over, live in the community, function independently, and have no chronic medical conditions. The Vantaa 85+ Study [31] recruited all people at least 85 years of age living in the city of Vantaa, Finland. Two Swedish studies have used a similar approach to recruiting: one recruited all 95+ year olds registered in the city of Göteborg [48], the other recruited all 90+ year old inhabitants of the Kungsholmen district [49].…”
Section: Investigations In the Oldest-oldmentioning
confidence: 99%
“…To elucidate the etiology of AD dementia, attempts have been made to correlate cognitive dysfunction with the classical neuropathological changes in AD, extracellular β-amyloid (Aβ) plaques, intraneuronal neurofibrillary tangles (NFTs), and synaptic/neuronal loss. However, some studies suggest that plaques and NFTs may not directly cause AD dementia since both pathologies can manifest in brains of patients that are not cognitively impaired [10,14,49,56]. Another potential mechanism underlying dementia is synaptic loss, since synaptic markers are decreased in AD brains [16,54,59,62].…”
Section: Introductionmentioning
confidence: 99%